2(j+7)=44

Simple and best practice solution for 2(j+7)=44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(j+7)=44 equation:


Simplifying
2(j + 7) = 44

Reorder the terms:
2(7 + j) = 44
(7 * 2 + j * 2) = 44
(14 + 2j) = 44

Solving
14 + 2j = 44

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + 2j = 44 + -14

Combine like terms: 14 + -14 = 0
0 + 2j = 44 + -14
2j = 44 + -14

Combine like terms: 44 + -14 = 30
2j = 30

Divide each side by '2'.
j = 15

Simplifying
j = 15

See similar equations:

| (2)(-4)(1)(-6)(5)= | | x+x+15=19 | | 7(-2+2)-3+-2= | | -4x^2+48x-128=0 | | 3x+x=84 | | -85-(-58)= | | (3w+4p)(3w-4p)= | | 7(x+2)-3+x= | | x+25+3x=-21-3x-24 | | x(x+1)=4 | | 8*-7+7-5*-7-3= | | 2b=0 | | 0.6d+9=57 | | 5x+x=252 | | 5x*56-78x/5=4 | | 2x+5x=252 | | 6w=3 | | 1.4x=11.2 | | 15c=300 | | 8x+7-5x-3= | | 2x+1700=59800 | | 0.3c=1.8 | | x(x-6)=-8 | | 9-(-3)+(-6)-(8)= | | 20=5d | | 2x-4=60 | | 10a^4-5a^2+15= | | 6x-48=2x | | 3.6=6m | | 6x-48=x | | 6x-37-36=5 | | 6-37-36+5=x |

Equations solver categories